2023
DOI: 10.1108/sgpe-12-2021-0088
|View full text |Cite
|
Sign up to set email alerts
|

Exploring motivation and satisfaction in part-time PhD students

Abstract: Purpose This study aims to explore the motivation and satisfaction of part-time PhD students in the USA through the lens of self-determination theory (SDT). Design/methodology/approach Following an explanatory sequential mixed methods design, data sources consisted of a survey (N = 100) and focus groups (N = 20) of part-time PhD students. Findings Findings suggest that part-time PhD students achieve greater satisfaction when they are autonomously motivated. Part-time PhD student satisfaction may be increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The supervisor's coaching (of the mesosystem) and guidance help students feel more confident in their own capacity to conduct research and publish academic articles. A high level of motivation was observed by the students during the coursework phase, however, this motivation dropped during the thesis writing and comprehensive examination phases (Sverdlik and Hall, 2020;Turner, 2023). A Ph.D. motivation scale was developed by Litalien and Guay (2015) using SDT to assess the importance of students' autonomous regulation over controlled regulation in assessing program satisfaction and performance.…”
Section: Intrinsic Motivationmentioning
confidence: 99%
“…The supervisor's coaching (of the mesosystem) and guidance help students feel more confident in their own capacity to conduct research and publish academic articles. A high level of motivation was observed by the students during the coursework phase, however, this motivation dropped during the thesis writing and comprehensive examination phases (Sverdlik and Hall, 2020;Turner, 2023). A Ph.D. motivation scale was developed by Litalien and Guay (2015) using SDT to assess the importance of students' autonomous regulation over controlled regulation in assessing program satisfaction and performance.…”
Section: Intrinsic Motivationmentioning
confidence: 99%
“…While there is an understanding of the importance of faculty mentorship, less is known about the role of familial support exogenous to the university admissions process. Literature on graduate studies has considered the role of familial support within graduate education itself, after enrollment and on the desire for family formation (Main, 2022; McAvoy and Thacker, 2021; Turner, 2023). Qualitative evidence has shown that women perceive less familial support doing graduate school (Aldrich, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research has documented a potential misalignment between doctoral programs and career preparation in general (Golde and Dore, 2001) and in higher education administration (Turner, 2023), which is a low consensus field (Freeman et al , 2014; Renn, 2020). Scholars have called for careful and critical attention to the structure and purpose of the doctorate with the aim of ensuring that the preparation of scholars is attuned to the pressing social needs said scholars are called to address throughout their careers (Barnacle and Cuthbert, 2021).…”
Section: Review Of Literaturementioning
confidence: 99%